ASPEK PERTUMBUHAN IKAN LAYANG (Decapterus macrosoma) DI PANGKALAN PENDARATAN IKAN SANGGENG KABUPATEN MANOKWARI - Yusmina E. Randongkir; Fanny Simatauw; Tutik Handayani (Jurnal Sumberdaya Akuatik Indopasifik, 2018)
This study aimed to find the fish distribution in size, heavy - long, and factors condition. This research was doing in March until June 2015. The methods that used to measure are descriptive method and technique observation. The total of sample fish obtained as many as 500 tail. The measure ment of length distribution obtained for individuals male which ranges are 109 -303 mm and 125 – 299 for female. Based on the results of correlation analysis between the length and weight of the fish is all positive and very strong, female fish has a correlation coefficient value 0.6184 with coefficient of determination (R2) 0.3824 and male fish 0,5775 with coefficient of determination (R2) 0,3335. This means there is a close relationship between the weight and body length of the overpass. The result of regression test between the length and weight of the female flying fish is W = 0.0015L2.0321 and the male glider is W = 0.004327 L1.8417, followed by the test of value b (regression coefficient value) obtained b <3 which means the growth of fish pattern shown allometric negative. It means that the length of body rises faster than their weight. In term of factors condition Decapterus sp. Classified in less flattened fish.